Análise do trabalho de uma equipe multiprofissional em um Centro de Atenção Psicossocial Álcool e Drogas - Daniela Tonizza de Almeida (2012)
In the last ten years have been proposed new guidelines for healthcare of alcohol and drugs users, among which stand out: a shift from the apparatus psychiatric asylum for the creation of a psychosocial care network, where the Psychosocial Care Centers alcohol and drugs (CAPS ad) play a central role; changes in work design and the products of labor, favoring comprehensive care from the Harm Reduction Model perspective, organization of work in an interdisciplinary and horizontal involving personal manager, workers, users, their families and community. In this context, the general objective of the study was to understand how the collective work featuring a CAPS ad, with regard to the organization of the work process and the articulation of professionals with each other and with the network care, identifying the discussions of norms and values that permeate the work management. Empirical research was carried out in an ad CAPS II of the metropolitan region Belo Horizonte from a qualitative and ergological approach. Were conducted semi-structured interviews with workers and users, participant observation and documentary research. The results showed that the theoretical engagement with the political-institutional project by the workers and the management and maintenance of open space where there are established communication and cooperation between different knowledges favor the creation of collective strategies for coping with adversity. However, we identified some challenges to be faced for the consolidation of the new model: the reorganization of work in order to reduce the workload for some occupational categories and hierarchy of knowledge; addressing the demand of the population served by the department with amount of available workers and expansion of care devices in emergency service. Despite advances in network construction psychosocial care, we found that deficiency of devices urgent / emergency, psychosocial rehabilitation and processes of communication between the teams that make up the network leverages the suffering in daily management work.